2019
DOI: 10.1109/access.2019.2898936
|View full text |Cite
|
Sign up to set email alerts
|

Research on Customer Marketing Acceptance for Future Automatic Driving—A Case Study in China City

Abstract: This paper investigates the acceptance of intelligent driving vehicles in the Chinese market using Guangzhou City as an example and a field questionnaire investigation based on the innovation diffusion theory. First, we tested the reliability and validity of 2530 effective questionnaires in 2018. Second, the cognition, expectations, technical concerns, and prospective expectations data of consumers with respect to intelligent driving vehicles are analyzed statistically. Finally, T-test and Pearson's correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…To test the construct validity, the Kaiser-Meyer-Olkin (KMO) and Bartlett tests were applied following varimax orthogonal rotation and factor analysis. Generally, the data is appropriate for factor analysis when the KMO value is above 0.7, and the p value of Bartlett's test is significant at the 0.05 level, and the correlation matrix of the sample has a shared factor ( Wang et al., 2019 ; Zhang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…To test the construct validity, the Kaiser-Meyer-Olkin (KMO) and Bartlett tests were applied following varimax orthogonal rotation and factor analysis. Generally, the data is appropriate for factor analysis when the KMO value is above 0.7, and the p value of Bartlett's test is significant at the 0.05 level, and the correlation matrix of the sample has a shared factor ( Wang et al., 2019 ; Zhang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue driving endangers the driver and other traffic participants, as it declines the driving cognitive and driving skills, therefore resulting in misperception, misjudge, and misoperation. To ensure driving security and traffic safety, the driver must have a clear understanding of the driving condition and surrounding road environments all the time [35]. It requires the driver to continually adjust the head orientation and the fixation point of the eye.…”
Section: Motion State Parameter Extractionmentioning
confidence: 99%
“…To ensure the safety of autonomous vehicles, a holistic fleet deployment scheme from interdisciplinary perspectives should be established as proposed by Koopman and Wagner [22]. Wang et al investigated the acceptance of intelligent driving vehicles in Guangzhou and indicated that consumers focused on not only the developmental prospects but also the technological safety of intelligent driving vehicles [23]. With the rapid progress of IoV and VANET, there is a great deal of technologies involved in data analysis for automatic vehicles, which are described as follows.…”
Section: Data Analysis For Automaticmentioning
confidence: 99%